2021
DOI: 10.5500/wjt.v11.i10.421
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting futility of liver transplant in elderly recipients: A single-center experience

Abstract: BACKGROUND As the population of the United States ages, there has been an increasing number of elderly patients with cirrhosis listed for transplant. Previous studies have shown variable results in terms of the relative survival benefit for elderly liver transplant (LT) recipients. There may be factors that are associated with a poor post-transplant outcome which may help determine which elderly patients should and should not be listed for LT. AIM To identify factors as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Interestingly, the authors identified CHF to be strongly associated with poor outcomes. Although the results by Kleb et al [ 1 ] are compelling, they need to be interpreted with caution. The data presented have been retrospectively reviewed, but some important indexes to estimate frailty and comorbidities, such as the Charlston Comorbidity Index[ 4 ] and Liver Frailty Index[ 5 ] have not been calculated.…”
Section: To the Editormentioning
confidence: 98%
See 2 more Smart Citations
“…Interestingly, the authors identified CHF to be strongly associated with poor outcomes. Although the results by Kleb et al [ 1 ] are compelling, they need to be interpreted with caution. The data presented have been retrospectively reviewed, but some important indexes to estimate frailty and comorbidities, such as the Charlston Comorbidity Index[ 4 ] and Liver Frailty Index[ 5 ] have not been calculated.…”
Section: To the Editormentioning
confidence: 98%
“…We read with great interest the study from Kleb et al [ 1 ]. The authors analysed the outcome of 260 elderly patients (65 years old) undergoing liver transplantation (LT) with the aim of identifying features associated with futility, defined as death within 90 d post transplantation.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…[4] Despite this, the concept of futility permeates in liver transplantation studies and remains in the OPTN statement. [5][6][7][8][9][10][11] There remains no consensus in the literature as to what defines a "futile" transplant. Proposed definitions include 1-year mortality or graft loss, [12] 90-day mortality, [5,6] 90-day or in-hospital mortality, [7] posttransplant mortality > waiting list mortality, [8] 1-year mortality after retransplant, [9] and long-term survival of <50% at 5 years.…”
Section: Introduction To "Futility"mentioning
confidence: 99%
“…[5][6][7][8][9][10][11] There remains no consensus in the literature as to what defines a "futile" transplant. Proposed definitions include 1-year mortality or graft loss, [12] 90-day mortality, [5,6] 90-day or in-hospital mortality, [7] posttransplant mortality > waiting list mortality, [8] 1-year mortality after retransplant, [9] and long-term survival of <50% at 5 years. [10,11] A long-term survival of <50% at 5 years after transplant has been adopted as the metric of poor posttransplant outcomes in European countries, but is not specifically related to "futility."…”
Section: Introduction To "Futility"mentioning
confidence: 99%